The effects of English proficiency and social support on the self-esteem of South Korean international college students with early study abroad experience: The mediating role of acculturative stress - Kim, Jin A; Lee, Woon Kyung (Journal of International Students, 2025)
This study examines how English proficiency, social support, and acculturative stress influence the self-esteem of 241 Korean international college students with early study abroad experience who continue their education at institutions in the U.S. and Canada. Social support had a significant positive direct effect on self-esteem. English proficiency and social support were negatively associated with acculturative stress, resulting in higher levels of self-esteem. Despite early study abroad, acculturative stress remains a key factor affecting self-esteem. The results suggest that professionals working with international students should not only focus on providing resources to enhance English language learning but also offer various forms of social support to foster a sense of belonging, ultimately facilitating a successful adjustment to the host culture. Further implications are discussed.